Creating new learning environments in virtual reality: Perceptions of English student-teachers - Virginie Privas-Bréauté (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This article focuses on pre- and in-service English teachers’ perceptions of the educational potential of virtual reality (VR). We consider VR as an educational device inscribed in embodied cognition theories and enhancing learners’ engagement and motivation through immersion and sensory-motor agency in teaching/learning situations. After pedagogical experiments with master’s degree students in English teaching/learning, the latter were asked to share their perceptions of VR in the context of language education. The data includes responses to pre- and post-intervention questionnaires as well as photos and videos taken during the trials of VR headsets and will shed light on the progress that still needs to be made if VR is used in language education.